Thyroid Dysfunction in Pregnancy and its Outcomes - Zakia Zaheen, Rukhsana Saboor, Zubaida Mujtaba, Sanobar Ashfaq Siddiqui, Shahla Channa (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate thyroid dysfunction in pregnancy and its outcomes. Study design: Descriptive study Place and duration of study: Department of Obstetrics & Gynaecology, Unit IV, Liaquat University of Medical & Health Sciences, Jamshoro from 1st January 2021 to 31st December 2021. Methodology: Two hundred females between 18-41 years were registered in the outdoor patient in their 10th week of pregnancy. A 2cc blood was withdrawn, serum separated and stored at -20ºC until analysis. Results: The mean age was 26.9±2.6 years. The women who were having hypothyroidism or hyperthyroidism had various complications during their pregnancy with 100% of them presenting depression and fatigue. There were 6.6% pregnant women suffering from hypo or hyperthyroidism who suffered miscarriages. Conclusion: Hypothyroidism/hyperthyroidism is prevalent in South Asian women and related with pregnancy complication and negative pregnancy outcomes in females.